Nivolumab Causing a Polymyalgia Rheumatica in a Patient With a Squamous Non–Small Cell Lung Cancer - Bernier, Marjorie; Guillaumé, Cyril; Léon, Nathalie; Alexandre, Joachim; Hamel-Senecal, Léa; Chrétien, Basile; Lecaignec, Florian; Humbert, Xavier; Fédrizzi, Sophie; Madelaine, J.; Sassier, Marion (Journal of Immunotherapy, 2017)
The anti-programmed cell-death-1 antibody, nivolumab, has been recently approved for the treatment of advanced non-small cell lung cancer. Although, today, immune-related adverse effects such as dermatologic, digestive, hepatic, and endocrine toxicities are well-known with immune checkpoint inhibitors, rheumatic diseases are less well described. Herein, we report the case of a patient without a history of arthritis who developed polymyalgia rheumatica after 13 cycles of nivolumab used for the treatment of advanced non-small cell lung cancer. Laboratory evidence of inflammatory syndrome, articular echography, and clinical presentation with classical symptoms and also distal manifestations were suggestive of this chronic inflammatory disorder. Because of a relevant pain, clinicians were forced to suspend immunotherapy. Nevertheless, due to glucocorticoid therapy, the patient's symptoms have decreased progressively. Moreover, nivolumab was reintroduced 8 weeks later, whereas prednisone (10 mg) was continued, without any recurrence symptoms. To conclude, our case suggests that polymyalgia rheumatica might be a very disabling anti-programmed cell-death-1 immune-related adverse effect.